Protocol to develop and pilot a primary mental healthcare intervention model to address the medium- to long-term Ebola associated psychological distress and psychosocial problems in Mubende District in Central Uganda (the Ebola+D project). - Leticia Kyohangirwe; Richard S Mpango; Christine Tusiime; Rwamahe Rutakumwa; Joshua Ssebunnya; Andrew Obuku; Barbra Elsa Kiconco; Isaac Sekitoleko; Hafsa Sentongo; Kenneth Kalani; Wilson Muhwezi; Giulia Greco; et al. (PLoS ONE)
Trial registration ClinicalTrials.gov NCT06093646.